Milk matters: offspring survival in Columbian ground squirrels is affected by nutrient composition of mother's milk - Skibiel, Amy L.; Hood, Wendy R. (Frontiers in Ecology and Evolution, 2015)
Through maternal effects, information about environmental conditions experienced in the maternal generation can be transmitted to subsequent generations. Although maternal effects have been described and quantified in many mammalian species, the underlying causal links are often under-studied. The close association between mother and neonate during the extended period of lactation in mammals provides a unique opportunity for mothers to influence offspring phenotype through nutrient provisioning of milk. The purpose of this study was to examine sources of inter-individual variation in milk composition and impacts on offspring phenotype and survival. Variation in fat content, protein content, and energy density of mother’s milk was associated with timing of reproduction. Mothers with intermediate birthdates produced milk that was higher in fat and energy density, but lower in protein than females with early or late birthdates. In turn, the pattern of change in milk composition affected juvenile overwinter survival. The protein content of Columbian ground squirrel milk typically increases to peak lactation and then declines before weaning. Pups consuming milk that was lower in protein in early lactation but then relatively high in protein at peak and late lactation had a higher probability of survival overwinter. Our results indicate that the interplay between the timing of reproduction and lactation performance has consequences for maternal and offspring fitness.